Presupuestos Participativos del GAD Municipal de Loja y su incidencia en la cobertura y calidad de Servicios Básicos en las Parroquias Rurales Noroccidentales, Zona 1 y 2 del Cantón Loja, periodo 2015 - Iñiguez Castro, Jaime Andrés (2016)
The main objective of this research is to "determine the incidence of the participatory budget in the coverage and quality of basic services (potable water, sewage, environmental sanitation) in the different rural parishes north-west of Canto Loja." The Constitution of Ecuador, as well as Laws, and Ordinances speak of the elaboration of participatory budgets and the participation of the citizenship to them. For the present investigation, it was proposed to develop three specific objectives: "To determine the degree of participation of rural parochial gads north-western Zone 1 and 2 in the elaboration of the participative budget of the municipal gad"; "The relationship between the planned participatory budget and the participatory budget implemented in social development projects directed to the rural north-western parishes, Zone 1 and 2"; And "coverage and quality of basic services in rural north-western parishes, Zone 1 and 2." The methodology used in this research was the deductive, statistical method and the techniques of bibliographic compilation, survey and interview. The results obtained were: in the participation of the elaboration of the participative budgets of the municipal gad, the 8 presidents of the rural parishes in the northwest mention that the participation is regular, that is to say less than 50%, and on the part of the citizens the 95,96 % Had not participated in the elaboration of participatory budgets in order to raise their needs; on the other hand, the ration between the planned participatory budget and the one executed, 51.54% was executed from the planned budget for social development projects directed to the parishes Rural and north-west, and therefore the coverage and quality of basic services is almost nil and there is a difficult 79.79% finally the conclusions and recommendations were made.It is pertinent to specify that the development of the present investigative process was carried out in compliance with the provisions of the Academic Regime Regulation of the National University of Loja and the Guidelines for the presentation of the Final Thesis Report of the Public Administration Career.